Pengaruh Influencer Marketing terhadap Sikap dan Keputusan Pembelian Produk Lifestyle - Ni Putri; Nyoman Amrita; Ni Dewi; Ni Loniawati; Kadek Karisma (Penerbit Jurnal Indonesia, 2025)
The objective of this study is to examine how marketing through influencers shapes consumer perceptions and purchasing behavior within the lifestyle product sector. A quantitative descriptive approach was applied, with information gathered via surveys administered to individuals who actively engage on social media and have encountered influencer-related content. The collected responses were processed using descriptive techniques, standard assumption evaluations, and a basic linear regression model. Findings indicate that influencer-driven promotion exerts a significant and positive impact on both consumer attitudes and their buying decisions. Consumers tend to develop higher levels of trust and a more favorable perception of products when they are promoted by influencers they consider credible and relevant. The findings also indicate that influencer marketing plays an important role in strengthening product image and encouraging purchase interest, particularly in the lifestyle product market, which is strongly influenced by trends, personal identity, and social media exposure.This study concludes that the selection of appropriate influencers and the creation of consistent and engaging content are crucial factors in implementing an effective and sustainable digital branding strategy. he findings from this study are anticipated to deliver useful understandings for businesses in designing influencer marketing strategies to enhance consumer trust and purchasing behavior.